Penerapan Teknik Editing L Cut dan J Cut dalam Video Feature Merangkai Tradisi dan Eksplorasi Modern Tarawangsa Sumedang - Syahrul Ramadhan; Santi Susanti; Heru Ryanto Budiana (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Tarawangsa is a traditional musical instrument from West Java that has distinctive sound characteristics and is often used in various traditional ritual ceremonies. However, in the modern era, the younger generation's interest in this cultural heritage has begun to fade due to the dominating influence of contemporary music. The purpose of writing this report is to explain the application of L Cut and J Cut editing techniques in the video feature Merangkai Tradisi dan Eksplorasi Modern Tarawangsa Sumedang and to introduce and preserve Tarawangsa music through collaboration with modern music that can attract the attention of the younger generation without losing its traditional essence. The method of creating this video feature includes three stages, namely the pre-production stage or designing and planning the work, the production stage or recording visual and narrative elements, and the post-production stage or editing and finalizing the work. The result of the application of these techniques is a video that is not only visually appealing, but also able to convey messages effectively about the preservation of Tarawangsa music. In conclusion, the use of L Cut and J Cut in the video feature Merangkai Tradisi dan Eksplorasi Modern Tarawangsa Sumedang can convey the message of culture, history, and preservation of the Tarawangsa Arts in a more dynamic and fun way.